Evaluation of antioxidant defense markers in relation to hormonal and insulin parameters in women with polycystic ovary syndrome (PCOS): A case-control study. Issue 3 (May 2019) - Fatima, Qudsia; Amin, Shajrul; Kawa, Iram Ashaq; Jeelani, Humira; Manzoor, Saika; Rizvi, Syeed Masuma; Rashid, Fouzia
Abstract: Aim: Polycystic ovary syndrome (PCOS) is a composite heterogeneous condition with multifactorial etiology like genetic, environmental factors and oxidative stress. The exact pro-oxidant and antioxidant status in PCOS patients has not yet been fully established. We designed prospective study aimed to explore the association of PCOS and oxidative stress and examine the relationship of oxidative stress biomarkers with insulin parameters. Methods: Two groups were included: study group including 85 women with PCOS and control group of 85 healthy volunteers. Biochemical, Hormonal and insulin parameters were measured. Vitamin C, vitamin E, nitric oxide and activities of antioxidant enzymes were estimated using spectrophotometric methods. Results: Subjects with PCOS had poor antioxidant status as reflected by significantly low levels of glutathione, vitamin C & E and considerably increased activities of antioxidant enzymes like glutathione peroxidase, glutathione reductase and glutathione transferase as compared to those without PCOS. At the same time insulin levels were found to be significantly high and a positive correlation between oxidative stress and insulin parameters was observed in PCOS. Conclusion: Low levels of antioxidants and increased oxidative stress with insulin resistance along with the observed correlation between these parameters suggest that women with PCOS are under oxidative stress which supports the concept that oxidative stress is involved in PCOS pathophysiology. Thus oxidative stress could be a contributory factor to future cardiovascular disease risk in these women in addition to known features like dyslipidemia, central obesity, etc.